PEMULIHAN KEBERFUNGSIAN SOSIAL WARGA KAMPUNG AMBON CENGKARENG JAKARTA BARAT DARI PENYALAHGUNAAN NARKOBA MELALUI METODE PENGEMBANGAN MASYARAKAT (COMMUNITY DEVELOPMENT) - Hudawami, Hudawami (Jurnal Insani, 2018)
Drug abuse in Indonesia is a social phenomenon that has become a serious problem. For this reason, comprehensive treatment is needed, especially for addicts and drug abuse. As mandated by law, addicts and victims of drug abuse must be given care and treatment until healed. Like the social problems that occurred in the Ambon Cengkareng Complex in West Jakarta, this problem has been going on for quite a long time, therefore it needs serious handling, one of which is to conduct social interventions with community development methods. The involvement of the government, community organizations and local communities is a very important element in the implementation of this intervention model. The purpose of social intervention is to restore social functioning both individually and in groups